STRATEGI PERCEPATAN PERTUMBUHAN EKONOMI KOTA BANDAR LAMPUNG - Ardiansyah, Muhammad; Handayani, Agustuti; Sunlinawati, Henny (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2025)
This article examines strategies for accelerating economic growth in Bandar Lampung City using a descriptive qualitative approach based on the analysis of regional and national policy documents. The background of this study lies in the city’s 2023 economic growth performance, which reached only 4.99%, falling short of the target set by the Regional Medium-Term Development Plan (RPJMD). The study identifies several structural challenges, including fragmented programs among government agencies, weak inter-sectoral coordination, limited integration between planning and implementation, and minimal involvement of non-government stakeholders. To frame these challenges, three theoretical perspectives are applied: Romer’s endogenous growth theory emphasizes the role of innovation, knowledge, and investment in human capital; Porter’s competitive advantage theory highlights the importance of local industrial clusters in enhancing regional competitiveness; and collaborative governance theory by Ansell and Gash stresses the need for multi-actor engagement in public policy processes. Findings indicate that the city’s sectoral potential remains underutilized, and coordination mechanisms are still largely symbolic. The article recommends integrative strategies that include strengthening institutional synergy, revitalizing key local economic sectors, and developing participatory, data-driven collaborative platforms. These strategies are aligned with the broader national development framework as outlined in the 2020–2024 RPJMN and the Sustainable Development Goals (SDGs), and are expected to contribute to more inclusive, adaptive, and sustainable economic growth at the city level. Keywords: Collaboration; Endogenous Growth; Industrial Cluster; Regional Economy